STUDI EVALUASI PEMADAMAN PADA JARINGAN DISTRIBUSI TENAGA LISTRIK 20 kV - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
PT. PLN (Persero) is a company engaged in the field of electricity supply. PLN is required to distribute electrical energy reliably and in accordance with the level of quality of service that has beendetermined. Therefore, it is necessary to evaluate the extent outage with SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interruption Frequency Index). With SAIDI can be taken remedial measures subsystems, both components or equipment. Whereas with SAIFI can be taken remedial measures to overcome burnout procedure and speed up the repair time. In this research will be discussed, the calcution of the level of reliability (SAIDI, SAIFI) and the power loss is not channeled by interference outages in PT. PLN (Persero) Region Substation Feeder Simpang Haru Polamas 2015.